Severe Thrombocytosis in a Newborn with Subcutaneous Fat Necrosis and Maternal Chorioamnionitis. (22nd February 2020) - Sahni, Mitali; Patel, Pooja; Muthukumar, Akila
Abstract : Background . Subcutaneous fat necrosis (SFN) is a form of transient panniculitis that presents commonly in infants with a history of perinatal insult, particularly hypothermia. It is characterized by subcutaneous nodules and plaques that appear over bony prominences on cheeks, shoulders, buttock, and thighs. SFN is usually associated with various complications including hypercalcemia, thrombocytopenia, hypertriglyceridemia, and hyperglycemia. Case Presentation. We present a unique case of a female infant with a history of maternal chorioamnionitis who presented with SFN at 11 days of life with thrombocytosis. The platelet count decreased during the hospital stay, and thrombocytosis resolved over the course of the next two weeks. She did not have any other hematological or metabolic abnormalities associated with SFN. Conclusion . Infants with perinatal stress are at increased risk of developing SFN during the first month of life. Infants with a diagnosis of SFN should be monitored closely for various hematological and metabolic abnormalities that can have serious consequences.